Consecutive Silver(I) Ion Incorporation into Oligonucleotides containing Cytosine‐Cytosine Mispairs. Issue 2 (2nd December 2020) - Hossain, M. Nur; Ahmad, Syed; Kraatz, Heinz‐Bernhard
Abstract: Invited for this month's cover is the group of Prof. Heinz‐Bernhard Kraatz from the University of Toronto, Canada. The cover picture shows the consecutive incorporation of Ag I ions into a DNA duplex containing adjacent C−C mispairs. Read the full text of the article at 10.1002/cplu.202000607 . Abstract : "We have demonstrated the consecutive incorporation of Ag I ion into dsDNA containing adjacent C−C mispairs. These findings demonstrate that metal ion mediation of nucleobase mispairs plays an important role in the structural changes/potential aggregation of DNA duplexes and to change their electrochemical properties". Read more about the story behind the cover in the Cover Profile and about the research itself at 10.1002/cplu.2012000607 .